Menduga Bobot Badan Sapi Bali Jantan Berberat di Atas 500 Kilogram (THE ESTIMATION OF LIVE WEIGHT OF BALI BULLS ABOVE 500 KILOGRAMS) - Sampurna, I Putu; Batan, I Wayan (Jurnal Veteriner, 2016)
Menduga Bobot Badan Sapi Bali Jantan Berberat di Atas 500 Kilogram   (THE ESTIMATION OF LIVE WEIGHT OF BALI BULLS ABOVE 500 KILOGRAMS)
Keywords: Bali bulls; live weight; regession; estimation